2010
DOI: 10.1016/j.alcohol.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption among patients with hepatitis B infection in northern Portugal considering gender and hepatitis B virus genotype differences

Abstract: Alcohol abuse is an important public health problem. In Portugal with a population of 10 millions of inhabitants, there are around 10% of alcoholics or excessive alcohol drinkers and 1% of chronically infected patients with hepatitis B virus (HBV). To examine the characteristics of patients with higher levels of alcohol consumption and to investigate the association between alcohol consumption and liver damage a total of 298 chronically infected individuals, with HBV genotyped and submitted to liver biopsy, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The analysis showed that patients classified as Child–Pugh grade B were older ( P = 0.001) and had a significantly higher percentage of alcohol intake above 20 g/day ( P = 0.004) when compared to individuals classified as Child–Pugh grade A. The same trend has been observed previously when studying the relationship between the severity of liver disease and age and alcohol consumption [Mota et al, 2010]. While this previous study reported a relationship between alcohol consumption and liver disease severity, a relaxed definition of liver disease was used, including patients with and without histological evaluation, and patients without disease reports.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The analysis showed that patients classified as Child–Pugh grade B were older ( P = 0.001) and had a significantly higher percentage of alcohol intake above 20 g/day ( P = 0.004) when compared to individuals classified as Child–Pugh grade A. The same trend has been observed previously when studying the relationship between the severity of liver disease and age and alcohol consumption [Mota et al, 2010]. While this previous study reported a relationship between alcohol consumption and liver disease severity, a relaxed definition of liver disease was used, including patients with and without histological evaluation, and patients without disease reports.…”
Section: Discussionsupporting
confidence: 79%
“…The results of the study are part of a project in progress at a Portuguese university to characterize the epidemiological profile of the HBV in northern Portugal [Mota et al, 2009, 2010]. This study, within the ambit of a larger project, focuses on the epidemiological profile of liver damage, particularly cirrhosis, in patients infected chronically with HBV.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B surface antigen and/or anti‐HCV antibody were present in 13 out of 86 patients (10%) in one study, and anti‐HCV antibody was present in 72 out of 213 patients (34%) in another study . A combination of HBV/HCV infection and AC predisposed patients to a more severe disease with decreased survival . It seemed that the lack of effective controls for hepatitis viruses likely influenced the end results.…”
Section: Discussionmentioning
confidence: 99%
“…6 A combination of HBV/HCV infection and AC predisposed patients to a more severe disease with decreased survival. 26,27 It seemed that the lack of effective controls for hepatitis viruses likely influenced the end results.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Verschuere et al 23 report that the predominant subtypes in Europe are genotypes A and D. This is true also for Portugal, especially in the Northern region of the country. 14,15 In countries where endemicity is low, and in age groups not covered by mandatory vaccination, sexual transmission is more common among males, whereas intrafamilial transmission seems to predominate among females. 14,22 Vaccination is mandatory for all newborns in Portugal since 2000.…”
Section: Introductionmentioning
confidence: 99%